PENGARUH PENAMBAHAN CARBOXY METHYLCELLULOSE DAN WAKTU PEMASAKAN TERHADAP MUTU SELAI NANAS - Naomi Uli Arta Siagian; Abdul Rahim; Baharuddin Baharuddin; Ifall Ifall (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
Pineapple Jam Quality Quality is determined by CMC concentration factors and cooking time. This study aims to study the effect of the addition of CMC and the length of cooking on the quality of pineapple jam so that it can be accepted by consumers. This research was conducted at the Laboratory of Processing, Faculty of Agriculture, Alkhairaat University Palu and Agro-Industry Laboratory, Faculty of Agriculture, University of Tadulako Palu. This research was conducted using factorial experiments arranged in a Randomized Block Design with three replications. The first factor of CMC concentration consisted of treatments C1 = 0.5%, C2 = 1.0%, and C3 = 1.5%. The second factor is the length of cooking, namely drying T1 = 20 minutes, T2 = 25 minutes and T = 30 minutes. The data obtained were analyzed by variance, followed by the BNJ test at the 0.05% level with the parameters of the test of amendment, moisture content, ash content, dietary fiber content, vitamin C, total acid content, and organoleptic test. The results showed that the best combination was found in 0.5% CMC concentration with 20 minutes cooking time. The treatment characteristics of 0.5% CMC concentrations with a cooking duration of 20 minutes resulted in better pineapple jams including water content (46.60%), ash content (0.86%), vitamin C (14.30%), and organoleptic levels the best for the aroma of pineapple jam on the treatment of 0.5% CMC concentration with a cooking duration of 20 minutes obtained the highest panelist assessment score of (4.72) with the